2018
DOI: 10.1177/0363546518810517
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perianchor Cyst Formation Over Time After Rotator Cuff Repair: Influential Factors and Outcomes

Abstract: Background: There is a lack of knowledge about the changes in perianchor cysts over time and the factors related to perianchor cysts. Purpose: To evaluate the changes in perianchor cyst formation and anchor absorption over time after arthroscopic rotator cuff repair with a biocomposite suture anchor and to evaluate the factors affecting perianchor cyst persistence and their relationship with patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…These were comparable in terms of failed healing rate (13.2% vs. 15.0%), perianchor cyst formation (60.5% vs. 60.0%), and major anchor-related complications evaluated by radiology at 6.3 ± 0.9 and 7.8 ± 1.2 postoperative months, respectively. In the follow-up study, the formation of perianchor cyst decreased with time and was observed only in 7 patients (18.4%) at 18 months after surgery [ 25 , 27 ] On the other hand, Shin et al reported that the bony ingrowth into PEEK anchors occurred two times faster than biocomposite anchors [ 28 ]. The PEEK anchor used in the study was newly developed and open-vented to facilitate bony ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…These were comparable in terms of failed healing rate (13.2% vs. 15.0%), perianchor cyst formation (60.5% vs. 60.0%), and major anchor-related complications evaluated by radiology at 6.3 ± 0.9 and 7.8 ± 1.2 postoperative months, respectively. In the follow-up study, the formation of perianchor cyst decreased with time and was observed only in 7 patients (18.4%) at 18 months after surgery [ 25 , 27 ] On the other hand, Shin et al reported that the bony ingrowth into PEEK anchors occurred two times faster than biocomposite anchors [ 28 ]. The PEEK anchor used in the study was newly developed and open-vented to facilitate bony ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Ro et al 5 are similar to those of other studies in that perianchor cysts do not negatively affect clinical outcomes. 6,8,9 Reported rates of cyst appearance vary widely among studies (10.8%-56.6%). 5,6,8,9 This is probably because of the different definitions of perianchor cysts and different methods of detecting the cysts (plain radiographs, computed tomography, and magnetic resonance imaging).…”
mentioning
confidence: 99%
“…6,8,9 Reported rates of cyst appearance vary widely among studies (10.8%-56.6%). 5,6,8,9 This is probably because of the different definitions of perianchor cysts and different methods of detecting the cysts (plain radiographs, computed tomography, and magnetic resonance imaging). There are hypotheses regarding why cysts occur around the anchors, including foreign-body reaction, synovitis, and inflammation.…”
mentioning
confidence: 99%
See 2 more Smart Citations